Fasting Physiology and Therapeutic Diets: A Look Back to the Future - Bland, Jeffrey S. (Integr Med (Encinitas), 2019)
The evidence presented at this event demonstrated the multiple clinical benefits of fasting physiology and points toward a future in which the clinical applications of dietary approaches will be well understood and successfully utilized. The conference reflected the scope and breadth of current research efforts in this important clinical area. Clearly, the application of the important new concepts related to fasting physiology that are emerging will require the advocacy and participation of professionals who are well trained in the fields of clinical nutrition and personalized lifestyle medicine.